2001
DOI: 10.1046/j.1439-0418.2001.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences walking speed and walking activity of Trichogramma brassicae (Hym., Trichogrammatidae)

Abstract: Walking speeds and walking activities (walking time divided by total time) of Trichogramma brassicae were determined at 12, 16, 20 and 25°C. Walking speed was measured during a 5‐min period, and walking activity over a 4‐day period. Both walking speed and walking activity were strongly influenced by temperature. Walking speed increased linearly with the temperature and was twice as high at 20 as at 12°C. At 25°C, walking activity was high during the whole day, at 20 and 16°C it decreased during the afternoon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
4
29
2
1
Order By: Relevance
“…Biever (1972), Boldt (1974) and Suverkropp et al (2001) found a similar effect of temperature on the walking activity of T. evanescens, T. brassicae, T. minutum and T. semifumatum Perkins (Hymenoptera: Trichogrammatidae). Pak and van Heiningen (1985) compared the oviposition rates of T. maidis Pint.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Biever (1972), Boldt (1974) and Suverkropp et al (2001) found a similar effect of temperature on the walking activity of T. evanescens, T. brassicae, T. minutum and T. semifumatum Perkins (Hymenoptera: Trichogrammatidae). Pak and van Heiningen (1985) compared the oviposition rates of T. maidis Pint.…”
Section: Discussionmentioning
confidence: 74%
“…Temperature influences not only walking speed and walking activity (Suverkropp, Bigler, & van Lenteren, 2001), and flight activity (Forsse et al, 1992), but also parasitism (Maceda, Hohmann, & dos Santos, 2003;Pak & van Heiningen, 1985). In general, activity increases with higher temperatures until a certain optimal temperature is reached, after which activity decreases.…”
Section: Introductionmentioning
confidence: 99%
“…At 40 °C, the T. evanescens wasps died. Suverkropp et al (2001) observed a significant effect of the temperature on T. brassicae walking speed. At 20 °C the average walking speed was twice as high as at 12 °C.…”
Section: Introductionmentioning
confidence: 79%
“…This is defined as the fraction of females observed that were active at the moments of observation (Suverkropp et al, 2001) and was analysed at three temperatures (15, 20 and 25 °C). One day old infected and mated cured female T. atopovirilia wasps were placed into vials (75 mm long and 10 mm diameter) with a drop of honey and closed with cotton wool.…”
Section: Walking Activitymentioning
confidence: 99%
See 1 more Smart Citation